The correlation between knowledge level and adherence to antihypertensive medication consumption in hypertensive patients at Prolanis Sumobito Community Health Center - Achmad Taufiq; Heni Maryati (UPPM STIKES Pemkab Jombang, 2026)
Medication adherence is essential for controlling blood pressure in individuals with hypertension. However, the 2023 Indonesian Health Survey reported a non-adherence rate of 36.4%. One factor influencing non-adherence is the level of knowledge. This study aimed to analyze the relationship between knowledge level and adherence to antihypertensive medication at the Sumobito Community Health Center. A correlational analytical design with a cross-sectional approach was used, involving 60 participants selected through total sampling. Data were collected using the Hypertension Knowledge-Level Scale and the Morisky Medication Adherence Scale-8, both validated for reliability and validity. Data were analyzed using the Spearman Rank test in SPSS. The results showed a significant relationship between knowledge level and medication adherence (p = 0.010; p < 0.05). However, the correlation coefficient (-0.328) indicated a moderate negative relationship, suggesting that higher knowledge does not necessarily improve adherence. This may be influenced by factors such as forgetfulness, boredom, and the misconception that medication can be discontinued once patients feel healthy. These findings suggest that health workers at the Sumobito Community Health Center should conduct regular monitoring and evaluation to improve adherence, including the use of pill boxes or pill cards.